(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
Benzylation of isomeric xylenes with benzyl alcohol in the presence of sulfuric acid as catalyst was studied and benzyl xylenes obtained in high yield. The effects of the variation of reaction parameters such as temperature, molar ratio of xylene to benzyl alcohol, amount of sulfuric acid and time of reactions were investigated. The yield of the products increased with the increase of each of the above-mentioned parameters. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15417 Bangladesh J. Sci. Ind. Res. 48(1), 75-80, 2013